„Angażująca nauka na studiach filologicznych” w opiniach nauczycieli akademickich (wyniki badania fokusowego) - Karolczuk, Marzanna; Sańczyk-Cruz, Anna; Wajda, Edyta (Acta Neophilologica, 2024)
The purpose of this study is to present academic teachers’ understanding of activities involving students in the teaching process in philology studies. The authors of the study conducted qualitative research collecting data through focus group interviews. This article discusses 11 codes assigned to the category “Engaging Learning at the University.” The results of this study showed that the understanding of engaging learning in philology studies corresponds to the latest trends in contemporary higher education. It was also found that the elements identified by teachers classified as “engaging learning” are more often instrumental and less frequently conscious and do not take into account the concept of transformative learning.